2018
DOI: 10.1002/2475-8876.10016
|View full text |Cite
|
Sign up to set email alerts
|

Super‐detailed FEM simulations for full‐scale steel structure with fatal rupture at joints between members—Shaking‐table test of full‐scale steel frame structure to estimate influence of cumulative damage by multiple strong motion: Part 1

Abstract: There have been several studies on analyses using finely meshed finite‐element (FE) models to understand in detail the behaviors of buildings during severe earthquakes. The accuracy of such analyses is often validated by comparing the results to the corresponding full‐scale shaking‐table test. While this approach is highly successful in terms of accuracy, no studies have considered the effect of fractures of members. In this study, numerical analyses are conducted for a steel structure subjected to multiple se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…Contact condition was considered for adopting to parts that was actually in contact between separated members. The further modeling details are described in previous studies [3], [4]. It is confirmed that natural periods obtained by eigenvalue analysis using this model agree with observed result of the actual specimen in the previous study [3].…”
Section: Finite Element Model and Computational Resourcessupporting
confidence: 88%
See 4 more Smart Citations
“…Contact condition was considered for adopting to parts that was actually in contact between separated members. The further modeling details are described in previous studies [3], [4]. It is confirmed that natural periods obtained by eigenvalue analysis using this model agree with observed result of the actual specimen in the previous study [3].…”
Section: Finite Element Model and Computational Resourcessupporting
confidence: 88%
“…Miyamura et al report that nonlinear behavior of shaking table test of a 4-story steel building can be replicated by using a fine meshed FE model with solid elements [1]. The authors also report about FE analysis examining a full-scale shaking table test of a 3-story steel structure that is the analytical target of this paper modeling mainly shell elements [2], [3]. These reports conclude that FE models that are finely meshed to reproduce the entire shape of structures as precisely as possible can appropriately replicate non-linear behaviors of building structures under earthquake excitations.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations